Experimental assessment of rodent control on two poultry farms of central Argentina - Gómez Villafañe, I.E. (2009)
We experimentally assessed the effect of controlling vegetation height along farm perimeters on the abundance of rodents in 2 broiler poultry farms in central Argentina. We carried out an experimental design based on the before-after-control-impact method. After vegetation treatments, there was a significant decrease in rodent abundance at the perimeter of the farm with control of vegetation height because of the reduction of the Pampean grassland mouse Akodon azarae. In poultry houses, there was a significant decrease in rodent abundance on nonaffected farms because of the reduction of the commensal house mouse Mus musculus domesticus, possibly because of a major collocation of rodenticide. Our results indicate that both the control of vegetation growth at the perimeters and the appropriate timing of rodenticide applications are effective measures for rodent control on broiler poultry farms when both control measures are applied simultaneously. We achieved effective rodent control through an understanding of the habitat use and population dynamics of the species involved and the characteristics of the area where the control program would be applied. © 2009 Poultry Science Association, Inc.